John Dewey’s Pragmatic Conceptions upon American Progressive Education and Ralph Waldo Emerson`s Transcendentalist Conceptions on American Literary Theory (A Comparative Approach) - Lucian Radu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This paper represents a comparative approach from the pragmatic and transcendentalist perspectives upon the American Progressive Education, respectively American Literary Theory, illustrated in John Dewey’s and Ralph Aldo Emerson`s writings, starting with the concept of experience, child - as the central part of both conceptions, continuing with individuality, rejection of the past, emphasising the importance of action, activity, culture and language in both cases.